Characterization of adhesion associated surface properties of uropathogenic Escherichia coli - Bartková, G; Ciznár, I; Lehotská, V; Kernová, T (Folia microbiologica, 1994)
Escherichia coli was isolated from the urine of patients with pyelonephritis, with urinary tract infections other than pyelonephritis and with asymptomatic bacteriuria. Surface properties of the strains were analyzed by the salting-out aggregation test (SAT), hydrophobic interaction chromatography (HIC), Congo red binding (Crb), agglutination of erythrocytes (MRHA) and latex particles covered by digalactoside (PF) and by adherence to tissue culture cells. In addition, a DNA probe for the pap gene was used. The DNA probe detected the highest proportion of strains with pap gene in the group of patients with pyelonephritis, lower in the urinary tract infections other than pyelonephritis and the lowest in the group with asymptomatic bacteriuria. Tests for P-fimbriae (PF, MRHA) showed a similar distribution. Hydrophobicity measured by SAT and by HIC did not show differences among the tested groups of strains. The results suggest that factors other than the P-fimbriae and hydrophobicity may contribute to the persistence of E. coli in the urinary tract.
Keywords: disacharidy; DNA Probes; Disaccharides; sacharidové sekvence; Pyelonephritis; Bacteriuria; infekce vyvolané Escherichia coli; Child; Bacterial Adhesion; Fimbriae, Bacterial; dítě; molekulární sekvence - údaje; Escherichia coli Infections; Escherichia coli; receptory buněčného povrchu; pyelonefritida; hemaglutinace; Urinary Tract Infections; bakteriurie; lidé; Genes, Bacterial; infekce močového ústrojí; Humans; Latex Fixation Tests; latex fixační testy; bakteriální fimbrie; Hemagglutination; Receptors, Cell Surface; Carbohydrate Sequence; DNA sondy; Molecular Sequence Data; bakteriální adheze; bakteriální geny